Stability Enhancement of Large-Scale Integration of Wind, Solar, and Marine-Current Power Generation Fed to an SG-Based Power System Through an LCC-HVDC Link - Wang, Li; Thi, Mi Sa-Nguyen (IEEE transactions on sustainable energy, 2014)
The integration of the renewable-energy power sources including solar, wind, and marine current with high penetration levels can have a negative impact on system stability. This paper presents an effective control scheme using a line-commutated high-voltage direct-current (LCC-HVDC) link joined with a damping controller based on adaptive-network-based fuzzy inference system (ANFIS) to achieve damping improvement of an integration of wind, solar, and marine-current power systems fed to a synchronous generator (SG)-based power system. The proposed ANFIS is an adaptive, robustness controller by combining the advantages of artificial neural network and fuzzy logic controller to face different operating conditions of the studied system. A time-domain scheme based on a nonlinear-system model subject to a three-phase short-circuit fault at the infinite bus is utilized to examine the effectiveness of the proposed control schemes. Comparative simulation results show that the designed ANFIS damping controller is shown to be superior for improving the stability of the studied system subject to a severe disturbance.